Impactos sócio-econômicos e ambientais da introdução da Tilápia do Nilo, Oreochromis niloticus, em açudes públicos do semi-árido nordestino, Brasi - Dias, Jandeson Brasil (2006)
The stocking of exotic fish, especially the tilapia, has become a common practice in the public reservoirs of the Brazilian semi-arid region. The stocking of tilapias has had as its main aim the improvement of the fisheries in the reservoirs and consequently the improvement of the socio-economic conditions of the families that have fishing as the main source of income. However, the environmental risks associated with this practice are high and can lead to a loss in aquatic biodiversity and to changes in the quality of the water. The object of this work was to quantify the socio-economic and environmental effects of the introduction of the Nile tilapia in the public reservoirs of the semi-arid northeastern Brazil. The analysis of the fish yield of 100 public reservoirs from 1970 to 2000 demonstrated that the introduction of the Nile tilapia apparently contributed to an increase in the total fish yield from the late 1970 s until the mid-1980 s. Nevertheless, from that time onwards the fish yield in these reservoirs has fallen into decline to levels inferior to those observed prior to the introduction of the tilápia. The analysis of the fishing activity statistics of the Gargalheiras reservoir located in the city of Acari, Rio Grande do Norte, demonstrated that the introduction of the Nile tilapia in the reservoir has not significantly increased the fish yield, the gross overall income, the gross per capita income nor the number of fishermen actively fishing in the reservoir. On the other hand, the analysis of the fishing activity statistics of the Gargalheiras reservoir has revealed a significant reduction in the captures of other commercially important fish species after the introduction of the tilapia. This result suggests that the Nile tilapia could have negatively affected other species of fish in the reservoir, contributing to the decline in their stocks. In order to assess the perception of the fishermen concerning the effects of the Nile tilapia over other species of fish and the quality of the water, questionnaires containing open and multiple choice questions were applied with 30 fishermen from the colony of the Gargalheiras reservoir. The great majority of the local fishermen stated that the tilapia is currently the most important species of fish to those who depend on fishing as a source of income and that they have not caused damage to other species of fish nor to the quality of the water in the reservoir. However, the results of the present work indicate that the alleged socio-economic benefits, employed to justify the introduction of the Nile tilapia in the reservoirs, are overestimated while the environmental impacts of the introduction of this exotic species are underestimated